A review of photochromism in textiles and its measurement. Issue 2 (3rd April 2017) - Periyasamy, Aravin Prince; Vikova, Martina; Vik, Michal
ABSTRACT: Photochromism is a light-induced reversible change in colour defined as: 'A reversible transformation in a chemical species between two forms having different absorption spectra brought about by photo-irradiation.' This issue of Textile Progress provides a review of photochromism, the different methods for producing photochromic textiles, their properties, the measurement of kinetic colour changes, and their application in photochromic textiles. Photochromism can be utilised in a variety of textile products from everyday clothing to high-technology applications such as protective textiles, medical textiles, geo-textiles and sports textiles. Although photochromic materials have been used since 1960 to cut down the transmission of light through the lenses in sunglasses, there has been limited further development since that time due to technical difficulties not only in the application of photochromic colourants, but also with the measurement of kinetic colour-changing properties. Renewed interest in photochromic textiles has arisen due to improved commercial potential in particular for applications as photochromic nanofibres, in 'smart' textiles and in 'smart' clothing.